Road Dust in Urban and Industrial Environments Sources, Pollutants, Impacts, and Management - Vlasov, Dmitry; Ramírez, Omar; Luhar, Ashok (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book brings together the results of field, experimental, and modeling studies related to road dust and its various size fractions as a key issue in understanding the relationships between several urban and industrial environments, and in the identification of pollution sources. The book is intended for professionals, researchers, and academicians who want to learn about new research findings regarding the chemical composition of road dust and its source, assessments of road dust and aerosol pollution levels (including express technique), environmental hazards and public health risks, the distribution of stable and radioactive isotopes in road dust, the determination of factors affecting the level of dust accumulation on roads and the intensity of its pollution, and the effect of road dust on the atmosphere and other environments. The book also provides data on some of the current challenges in studying road dust, including various aspects of the formation, transport pathways, and accumulation of road dust in urban, industrial and other areas.